Insight into the complex genetic network of tetraploid Atlantic salmon ( Salmo salar L.): Description of multiple novel Pax -7 splice variants - Gotensparre, S M; Anderssen, E; Wargelius, A; Hansen, T; Johnston, Ian Alistair (Gene, 2006)
Paired box transcription factor 7 (Pax-7) cDNA was isolated from the skeletal muscle and brain of alevin and adult stages of Atlantic salmon, identifying 10 variants categorised as novel or established insertions (ins) or deletions (del). Two putative Pax-7 paralogs were identified (denoted Pax-7 alpha and Pax-7 beta) on the basis of the length and sequences of intron 3 (218 and 248 bp) and versions of ins1 and ins2. Pax-7 beta contained a threonine variant of ins1 (GQY[T]GPEYVYCGT), and a shortened variant of ins2 (GEAS). Pattern identification revealed the threonine variant of ins1 includes a potential phosphorylation site (casein kinase 11). Thus, the tetraploid Atlantic salmon genome appears to contain at least two putative copies and multiple splice variants of Pax-7. In situ hybridisation localised Pax-7 to mononuclear cells in the fast muscle of adult Atlantic salmon, while quantitative real-time PCR showed Pax-7 alpha to be more highly expressed in brain than in skeletal muscle. (c) 2006 Elsevier B.V. All rights reserved.